Effects of Polyphenol Administration to European Farmed Sea Bass (Dicentrharcus labrax L.): Special Focus on Hepatopancreas Morphology - Magrone, Thea; Spagnoletta, Anna; Magrone, Manrico; Russo, Matteo A.; Corriero, Aldo; Jirillo, Emilio; Passantino, Letizia (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2019)
Background and Objective: Hepatopancreas is an accessory organ associated with the liver in some fish, even including sea bass (Dicentrharcus labrax L.). Hepatopancreas contains an exocrine portion but until now its function has poorly been investigated. Methods: Here, European farmed sea bass have been treated with a feed enriched in polyphenols extracted from seeds of red grape (Nero di Troia cultivar) at two different doses (100 and 200 mg/kg, respectively) from day 273 to day 323. In fish samples, hepatopancreas area sizes have been measured to evaluate the effects of this dietary regimen on its morphology. Results: Quite interestingly, in treated fish area sizes of hepatopancreas were higher than those detected in untreated fish. Two hundred mg dose of polyphenols was more effective than that of 100 mg/kg polyphenols. Finally, hepatic polyphenol concentration was diminished in fish receiving 100 mg dose polyphenols and normalized with 200 mg dose in comparison to untreated fish. This evidence suggests the utilization of polyphenols for liver function, even including hepatopancreas development. Conclusion: Our data suggest an expansion of hepatopancreas induced by polyphenol administration that is also associated with less mortality in farmed fish.
Keywords: hepatopancreas